Advertising in Instagram Social Media - Silvira, Melva; Riswanto, Riswanto (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2023)
Advertising is currently facing significant difficulties, whether people know the effect of the number of advertisements on advertising saturation. The public is presented with communication tools by the new era media. Anyone involved in advertising should be aware of this situation because the evolution of advertising is parallel to the new media movement. As a result, the expectations of the target market segment will be better met. A profession associated with a new style of advertising, driven by the appearance and popularity of social media, has responded to the challenges of today's new advertising style. utilizing social media as a new choice in communication strategies, such as Instagram social media which is a forum or place for building relationships, communicating with anyone and anywhere, showing pictures or short videos, expressing expressions using the available comments column, the function of Instagram social media is also a social media that builds a good image or picture in the process of marketing products or services offered by entrepreneurs or business people